Synthesis of Cellulose Acetate from Screw Pine (Pandanus tectorius) Leaves for Enhancing Water Permeability and Fouling Resistance of PVDF Membrane - Elyna Wahyu Trisnawati; Venty Suryanti; Edi Pramono; Indri Sri Cahyani; Diah Safriyani (Universitas Gadjah Mada, 2023)
Cellulose derivatives from natural resources continuously develop to find the best hydrophobic polymer-based membrane technology performance. This study was conducted to improve the hydrophilicity, performance, and anti-fouling of polyvinylidene fluoride (PVDF) membrane with cellulose acetate (CA) filler synthesized from screw pine (Pandanus tectorius) leaf cellulose. CA was synthesized by the Fischer esterification mechanism and the PVDF membrane was fabricated using the phase inversion method with 0.3% CA concentration. FTIR analysis of CA shows an absorption at 1700 cm−1 suggesting that the hydroxyl group of cellulose had been successfully substituted with an ester group (C=O), and CA has a high degree of substitution (DS) value of 3.50. Adding CA improved the hydrophilicity and anti-fouling properties of up to 86.45% of PVDF membranes. Furthermore, CA increased the value of water permeability 2–3 times than pristine PVDF membrane. The presence of CA enhanced the porosity of the PVDF membrane, which promoted the membrane's effectiveness for MB filtering. As a result, CA from screw pine leaf cellulose has promising features as a filler for PVDF membranes and potential dye filtration.